Carbon sources and trophic interactions of vent fauna in the Onnuri Vent Field, Indian Ocean, inferred from stable isotopes. (April 2022) - Suh, Yeon Jee; Kim, Min-Seob; Kim, Se-Joo; Kim, Dongsung; Ju, Se-Jong
Abstract: Food web structures (source and flow of energy in biological communities) are linked to ecological niche and species interactions, which are essential for assessing ecosystem stability and resilience. This study investigated the carbon fixation pathways of the source microbes and trophic relations of the benthic faunal community in the Onnuri Vent Field (OVF), Central Indian Ridge using sulfur (δ 34 S), carbon (δ 13 C), and nitrogen (δ 15 N) stable isotopic compositions. OVF megafauna exhibited a common isotopic pattern in hydrothermal vents with increasing δ 15 N and δ 13 C values, but not with δ 34 S values. Chemosynthetic production was the predominant source of energy in the OVF, and we identified at least three potential pools of isotopically distinct chemosynthetic production pathways, namely, the Calvin–Benson–Bassham cycle, reverse tricarboxylic acid cycle, and methanotrophic production. Within phyla, the endosymbionts and episymbionts of host taxa had different bacterial groups or carbon fixation pathways, indicating that they utilize non-overlapping resources, mutually benefiting themselves from less competition. We identified seven trophic guilds and four trophic levels in the OVF: (i) basal species consisting of symbiont host and bacterivores, (ii) intermediate species consuming particulate organic matter and detritus in addition to bacteria, (iii) scavengers and carnivores that specialize in few diets, and (iv) top predators of crab Austinograea rodriguezensis and Munidopsis sp. that are omnivorous. However, there were some spatial variations in energy sources of megafauna within the OVF, suggesting that source availability affect their trophic relations. We also found similarities and differences in the energy source and feeding relationship of some OVF fauna from those in other Indian Ocean hydrothermal vents. Overall, we believe that the results of this study contribute to improving our understanding of the nature and variation of food web structure and feeding strategies used by vent fauna for survival in the Indian Ocean hydrothermal vents that are particularly less explored. Highlights: Food web structure in the OVF is reconstructed using stable isotopes. Methanotrophs and thiotrophs are important primary producers in the OVF. Symbionts of host taxa have unique carbon niches or metabolic pathways. Trophic relations of vent fauna can be influenced by the environment.